2022
DOI: 10.1097/md.0000000000003588
|View full text |Cite|
|
Sign up to set email alerts
|

MRI features of testicular spermatic granuloma

Abstract: This is a meta-analysis to compare the results between laminoplasty and laminectomy followed by fusion for the patients with multilevel cervical compressive myelopathy. An extensive search of literature was performed in MEDLINE, Embase, the Cochrane library, CNKI, and WANFANG. The following outcome measures were extracted: the Japanese Orthopaedic Association (JOA) scores, cervical curvature index (CCI), visual analog scale (VAS), cervical lordosis (C2–7), complications, blood loss, and operation time. Data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
3
28
0
7
Order By: Relevance
“…Liu et al [33] showed that both techniques increased the JOA score postoperatively and resulted in similar improvements in the VAS score.…”
Section: Clinical Outcomementioning
confidence: 99%
See 4 more Smart Citations
“…Liu et al [33] showed that both techniques increased the JOA score postoperatively and resulted in similar improvements in the VAS score.…”
Section: Clinical Outcomementioning
confidence: 99%
“…A recent study by Liu et al [33] reported that both techniques resulted in no difference in postoperative cervical curvature index and cervical Cobb's angle. However, the authors [33] suggested to select laminectomy with fusion in severe preoperative cervical kyphotic patients.…”
Section: Radiological Outcomementioning
confidence: 99%
See 3 more Smart Citations